2021
DOI: 10.1371/journal.pone.0252209
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for acute kidney injury and mortality in high risk patients undergoing cardiac surgery

Abstract: Background Acute Kidney Injury (AKI) represents a clinical condition with poor prognosis. The incidence of AKI in hospitalized patients was about 22–57%. Patients undergoing cardiac surgery (CS) are particularly exposed to AKI because of the related oxidative stress, inflammation and ischemia-reperfusion damage. Hence, the risk profile of patients undergoing CS who develop AKI and who are consequently at increased mortality risk deserves further investigation. Methods We designed a retrospective study examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 48 publications
4
19
2
Order By: Relevance
“…Both previous studies and our study have shown that older age, anemia, perioperative red blood cell transfusions, and preoperative serum creatinine level were independently associated with kidney injury [ 5 , 9 , 18 , 19 ]. In our study, men were more likely to develop AKI than women, which concurred with the findings of several studies [ 11 , 16 , 20 ].…”
Section: Discussionsupporting
confidence: 54%
“…Both previous studies and our study have shown that older age, anemia, perioperative red blood cell transfusions, and preoperative serum creatinine level were independently associated with kidney injury [ 5 , 9 , 18 , 19 ]. In our study, men were more likely to develop AKI than women, which concurred with the findings of several studies [ 11 , 16 , 20 ].…”
Section: Discussionsupporting
confidence: 54%
“…Clinically, our study is motivated by previous research which indicates that the intraoperative use of CPB leads to a systemic inflammatory response that is induced by contact activation of blood due to the artificial surface of an extracorporeal system [ 47 , 48 , 49 ]. Although intraoperative complications in elective cardiac surgery are rare due to high operative standards [ 50 ], there is a 40% chance of developing post-surgery complications such as bleeding, pneumonia or acute kidney injury [ 51 , 52 , 53 , 54 ]. This generates the demand for sophisticated methods of detection for inflammatory processes in blood that are more closely associated with postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that prolonged cardiopulmonary bypass time and ACC time were also independent risk factors for postoperative complications of AKI in patients undergoing ONCAB [ 22 , 23 ]. Since renal blood flow and perfusion are relatively insufficient during extracorporeal circulation, massive erythrocytes were destroyed, and the released free hemoglobin consequently caused tubular obstruction and reduced glomerular rate filtration.…”
Section: Discussionmentioning
confidence: 99%